Awareness and perception of senior high school students on home economics - Lapuz, Edgar Raphael Abesamis; Trinidad, Mary Justine Clarise A. (Quezon City College of Home Economics, University of the Philippines Diliman, 2023)
This is a qualitative study that describes the awareness and perception of selected senior high school students (SHS) on home economics (HE). The factors influencing their perceptions were also determined. A survey with a list of home economics topics and competencies was answered by 320 randomly selected students using cluster sampling. Among these respondents, an in-depth open-ended interview was conducted to 21 of them to describe their current perceptions and identify the factors influencing these.
Results show that SHS students have limited awareness on home economics as they confuse topics from related-areas with the discipline such as agriculture and electronics to be taught under home economics. Students have limited awareness of HE’s presence as an undergraduate program with only 4 of 21 stating they were aware. In terms of perception, students perceived home economics to teach content focusing on cooking, the service industry, household matters, self-sufficiency, and skills enhancement. Delivering real life content, creating opportunities for employment, and producing capable citizens are the believed importance of home economics. Lastly, individuals in the home economics field were viewed to have similar drive and experiences with their peers in terms of interests and motivation, have different qualities compared to their peers in terms of creativity and being hardworking, and have career choices related to food and beverage service. The influence of these perceptions are varied and can be classified into school-related, peer-related, media-related and home-related experiences. The name of home economics was also found to contribute to its image positively as it was said to reflect the core of home economics which suggests that its name be retained contrary to discussions on wanting to change it.
Given the limited nature of awareness and perception of senior high school students, the study finds it necessary to devise accurate representation of home economics with the help of curriculum developers, teachers, home economists, and the education department in the country.
Thesis
Includes bibliographical references (pages 112-120)
Keywords: Home economics -- Philippines; High school students -- Philippines